2019
DOI: 10.1007/s42773-019-00031-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochar produced from Amazonian agro-industrial wastes: properties and adsorbent potential of Cd2+ and Cu2+

Abstract: In the Amazon region, several residues that have been misused can serve as feedstocks for biochar production with the aim of recovering soils contaminated by heavy metals. However, these biochars need to be firstly tested for their adsorption capacity as well as their physicochemical attributes prior to field application. Therefore, this study aimed to characterize and evaluate the adsorption capacities of Cd 2+ and Cu 2+ of biochars produced from acai (BA), Brazil nut (BN), and palm kernel cake (BK) residues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…The biochar yield of 27.8% means that, considering the production conditions used, for each 100 kg of açaí seeds, 27.8 kg of biochar can be produced. This is in agreement with Dias et al (2019) who tested the rate of biochar production under similar conditions and temperatures for different sources of biomass characteristic of the Amazon region, including açaí seeds (25.4% at 400 °C). The alternative kiln used here for the production of biochar proved to be efficient, since the production rates are similar to those of Sato et al (2019) under laboratory conditions.Considering the municipality of Belém in Brazil, with about 3000 establishments that process and sell fruit pulp, the daily demand is around 440 tons of the fruit in natura.…”
Section: Characteristics Of Açaí Seeds In Nature and After Pyrolysissupporting
confidence: 91%
“…The biochar yield of 27.8% means that, considering the production conditions used, for each 100 kg of açaí seeds, 27.8 kg of biochar can be produced. This is in agreement with Dias et al (2019) who tested the rate of biochar production under similar conditions and temperatures for different sources of biomass characteristic of the Amazon region, including açaí seeds (25.4% at 400 °C). The alternative kiln used here for the production of biochar proved to be efficient, since the production rates are similar to those of Sato et al (2019) under laboratory conditions.Considering the municipality of Belém in Brazil, with about 3000 establishments that process and sell fruit pulp, the daily demand is around 440 tons of the fruit in natura.…”
Section: Characteristics Of Açaí Seeds In Nature and After Pyrolysissupporting
confidence: 91%
“…Dias et al. (2019) evaluated the adsorbent potential of Cd 2+ and Cu 2+ by Brazil nut, açai, and palm kernel waste‐based biochars. The highest adsorption capacities were observed in biochars produced at the highest pyrolysis temperatures (700°C).…”
Section: Applications Of Brazil Nut Wastes In the Literaturementioning
confidence: 99%
“…The raw material used for biochar production is also one of the factors that can impart a lower P sorption capacity to biochar because, together with the pyrolysis temperature, it determines the formation of surface charges (Vandecasteele et al, 2017). This same type of biochar was evaluated by Dias et al (2019), who found a lower adsorption capacity than that of biochar produced from materials such as kernel and Brazil nutshells. Another factor related to lower P sorption is the presence of coexisting ions, which reduce P retention through competition (Ngatia et al, 2019).…”
Section: Influence Of Açaí Biochar and Compost On The Sorption And Desorption Of Pmentioning
confidence: 99%